(untitled) (Bangladesh Agronomy Journal, 2015)
A pot experiment was carried out under semi-controlled environmental condition in the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during December 2012 through March 2013 aiming to alleviate the salinity stress effects on chickpea using salicylic acid (SA) and gibberelic acid (GA3). Chickpea variety BARI Chola-5 was used in the experiment. Salt solution was prepared by adding tap water in sea water to make 5, 7.5 and 10 dS m-1 salinity level. Plants were irrigated with 5, 7.5 and 10 dSm-1 concentrations of saline water from 14th days after sowing (DAS) to maturity (100 DAS) and control plants were irrigated with tap water. Different concentration of SA (200 ppm and 400 ppm) and GA3 (10 ppm and 20 ppm) were applied as foliar spray once in a week from 20 DAS to flowering stage. The data for chlorophyll content in leaf and water relation traits such as relative water content (RWC) and water retention capacity (WRC) were measured 7 days after foliar spray of plant growth regulators at flowering stage. Total dry weight (root+shoot), yield and yield contributing characters were measured at maturity. Results indicated that salinity decreased total dry weight, chlorophyll content, relative water content, water retention capacity and yield of chickpea. Foliar application of SA and GA3 at different doses under different salinity conditions had the positive effects related to mitigation of salinity stress effect but low concentration i.e., SA and GA3 @ 200 ppm and 10 ppm, respectively were found to alleviate the adverse effects significantly on the above parameters at low salinity condition (5 dSm-1). Bangladesh Agron. J. 2015, 18(1): 81-88